Factors Influencing Nursing Management in the COVID-19 Situation of Nursing Administrators in University Hospitals, Northeastern of Thailand - Srijakkot, Jitpinan; Dapha, Sompratthana; Sookpier, Pornpimon; Juntachum, Wanchanok (Health Science Journal of Thailand, 2024)
This predictive research aimed to determine the level of nursing administration and factors influencing nursing administration in the situation of the COVID-19 epidemic among 122 nursing administrators who were head nurses or in higher positions at university hospitals in the northeast of Thailand. The research tools consisted of a questionnaire on environmental factors in work and a questionnaire on nursing management in the situation of the COVID-19 pandemic. The content validity values of the questionnaire were 0.96 and 0.98. The reliability values were verified by Cronbach’s alpha coefficient, which were 0.93 and 0.92. Data was analyzed by descriptive statistics and stepwise multiple regression analysis. The results showed the average score of nursing administrators in the situation of the COVID-19 pandemic of nursing administrators at university hospitals in the northeast of Thailand was at a high level. The COVID-19 pandemic situation was divided into 3 phases, including nursing management before, during, and after the COVID-19 pandemic, which had a high level in all 3 phases. In addition, the environmental factors in the work, consisting of the role perception of nursing administrator and the service support system, could jointly predict the variance of nursing administration in the situation of COVID-19 with a statistical significance of 82.50% (R2 = 0.825, p-value <0.05).